Landform evaluation through hypsometric characterisation: An example from a selected river basin in Southern Western Ghats, India - Hamza, Vijith; Prasannakumar, V.; Pratheesh, P. (2017)
© Kaunas University of Technology. Characteristics and spatial variation in geomorphic processes in the Meenachil river basin in southern Western Ghats, Kerala, India, is documented by analyzing the hypsometric parameters of 49 subwatersheds of the 5th, 4thand 3rdorder. Hypsometric curves and parameters such as hypsometric integral (Ea), maximum concavity (Eh), coordinates (a*, h*) of the curve-slope inflection point (I), and normalized heights of the hypsometric curve at 20%, 50% and 80% of the area indicate spatial variation. The longitudinal profile of the river shows a highly disturbed region, above a flow length of 20 km and a relatively less disturbed area downstream. The hypsometric integral classifies most of the subwatersheds into mature and mature-to-old age transition while varying shapes of the hypsometric curves imply the influence of tectonic uplift. Variation of hypsometric concavity in close spatial proximity also confirms the variation in the effect of tectonic processes in the region, where the combination of fluvial and diffusive process is active and are evident from the high hypsometric head and toe measurements. Repeated occurrences of earthquakes in the region confirm the presence of ongoing tectonic activities, which have direct bearing on the geomorphic characteristics of river basin.